ChemInform Abstract: Pd(0)‐Catalyzed 1, 1‐Diarylation of Ethylene and Allylic Carbonates. Issue 10 (11th March 2014) - Saini, Vaneet; Liao, Longyan; Wang, Qiaofeng; Jana, Ranjan; Sigman, Matthew S.
Abstract 1, 1‐Diarylalkenes are easily synthesized from a mixture of aryldiazonium tetrafluoroborates, arylboronic acids and olefins such as ethylene or allylic carbonates via a one‐step procedure.